miR-155 induces sepsis-associated damage to the intestinal mucosal barrier via sirtuin 1/nuclear factor-κB-mediated intestinal pyroptosis - Li Zhihua; Wang Yi; Huang Weiwei; Shi Xingyu; Ma Tao; Yu Xiangyou (Acta Biochimica et Biophysica Sinica, 2024)
Sepsis is a life-threatening state of organ dysfunction caused by systemic inflammation and a dysfunctional response to host infections that can induce severe intestinal mucosal damage. Pyroptosis is mediated by the activated NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome after stimulation by various inflammatory factors during sepsis. The inflammatory response is a major driver of intestinal damage during sepsis. Intestinal mucosal barrier dysfunction in sepsis is associated with pyroptosis, a type of programmed inflammatory cell death. Several studies have confirmed the role of miR-155 in sepsis and other diseases. However, the effect of miR-155 on intestinal pyroptosis in the context of intestinal mucosal barrier dysfunction during sepsis remains unclear. Thus, a model of sepsis in Sprague-Dawley rats is established using cecal ligation and puncture (CLP), and a series of molecular biological methods are used in this study. The results show that the expression of miR-155 is increased and that of sirtuin 1 (SIRT1) is decreased in the intestinal tissues of patients with sepsis. miR-155 expression is negatively correlated with SIRT1 expression. Increased miR-155 expression significantly inhibits SIRT1 activity and upregulates the expressions of NOD-like receptor family pyrin domain-containing 3 (NLRP3), caspase-1, apoptosis-associated speck-like protein containing a CARD (ASC), interleukin-1β (IL-1β) and interleukin-18 (IL-18) to promote pyroptosis. The inhibition of miR-155 expression is associated with increased SIRT1 expression, promotes the deacetylation of p65, and significantly downregulates p65 acetylation. Herein, we propose that miR-155 induces pyroptosis in the intestine partly by regulating SIRT1, thereby reducing the deacetylation of the nuclear factor (NF)-κB subunit p65 and increasing NF-κB signaling activity in sepsis, leading to intestinal barrier damage.